The Management of acute lateral ankle sprains: A survey of South African Surgeons and best evidence available - Wever, Stefan (Division of Orthopaedic Surgery, 2021)
Introduction: Ankle sprains remain the single most frequent injury in modern sports with increasing evidence that it is not as innocuous as previously thought. Conservative treatment options include various forms of immobilization such as casts, moonboots and stirrup braces, followed by a rehabilitation period involving different modalities. Despite clinical evidence there seems to be a divergence between research and practice with an increase in acute surgical repair especially with regards to professional athletes. Design: Descriptive cross-sectional survey analysis Aim of the study: To assess the approach on management of acute ankle sprains by orthopaedic surgeons in South Africa. Methods: A two part study. Firstly, a questionnaire was emailed to participating orthopaedic surgeons, consisting of eight treatment options for a grade 3 lateral ankle sprain in a non-professional athlete. Secondly, a literature review to establish the current best practice concerning ankle sprain management. Results: The total number of respones where 129 out of 719 that were sent out. Surgical repair was offered in 24 (19%). Conservative treatment including either cast or moonboot for a period of 6 weeks was chosen by 49 (38%) and 2 to 4 weeks by 55 (43%) as their preferred treatment. Only 39 (30%) of responding SAOA members chose a short period of immobilization followed by functional rehabilitation in accordance with the current best evidence available, based on the literature review done. Conclusion: Despite good clinical evidence there seem to be a lack of consensus in the management of grade 3 lateral ankle sprains.